Quad 2.0: Australia’s reaction to the ‘China threat’ - De Silva, Shakthi (UI Scholars Hub, 2023)
The prevailing scholarly consensus maintains that Australia’s rising threat perception of China influenced its decision to re-join the Quadrilateral Security Dialogue (Quad) in 2017. Although the minilateral initiative does not have a declared policy to inhibit China’s influence or curtail China’s aggressive behaviour in the Indo-Pacific region, scholars assert that the underlying rationalisation for its resurgence in the present context is due to China’s behaviour. The paper tests this hypothesis by examining whether Australia’s threat perception of China is manifest in its defence white papers and defence updates from 2000 to 2016. Having reviewed this primary material, the author concludes that Australia’s threat perception of China increased over time from the early 2000s. In particular, increased attention to China’s activities in the South Asia and Southeast Asia as well as Australia’s decision to closely observe the bilateral relationship between the United States and China after 2008, manifests Australia’s increased threat perception of China. This is also supported by Lowy Polls between 2000 and 2016. In sum, the paper concludes that Australia’s rising threat perception of China appears to have been a major factor influencing its decision to re-join the Quad in 2017.